2019
DOI: 10.1002/ece3.5368
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐tolerant native plants have greater responses to other environments when compared to salt‐tolerant invasive plants

Abstract: The strong expansion potential of invasive plants is often attributed to fast adaptive responses to stress. However, the evolution of tolerance to one stressor may affect the responses to other stressors. Currently, it remains unclear what effect the evolution to one stressor might have on the responses to other single or combined stressors. Moreover, it is unknown how this might differ between invasive and native species. Invasive plants ( Mikania micrantha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Previous research suggests that invasive populations may have: (1) lower stress tolerance than native populations (e.g., Dlugosch et al., 2015), (2) less optimal stress responses than native species (O'Connell & Savage, 2020), or (3) lower performance than native species under more extreme stress (Schumacher et al., 2008). Our findings together with earlier studies (e.g., Liu et al., 2019; Welles & Funk, 2021) indicate that relatively few highly successful invasive species have high baseline tolerance that makes adaptation less necessary when settling into stressful sites. For example, some invasive species do not show adaptation, but plasticity across various stressful sites, such as sweet vernal grass ( Anthoxanthum odoratum L., Platenkamp, 1990) in sites characterized by salinity, serpentine soils, and dryness (Table S1).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous research suggests that invasive populations may have: (1) lower stress tolerance than native populations (e.g., Dlugosch et al., 2015), (2) less optimal stress responses than native species (O'Connell & Savage, 2020), or (3) lower performance than native species under more extreme stress (Schumacher et al., 2008). Our findings together with earlier studies (e.g., Liu et al., 2019; Welles & Funk, 2021) indicate that relatively few highly successful invasive species have high baseline tolerance that makes adaptation less necessary when settling into stressful sites. For example, some invasive species do not show adaptation, but plasticity across various stressful sites, such as sweet vernal grass ( Anthoxanthum odoratum L., Platenkamp, 1990) in sites characterized by salinity, serpentine soils, and dryness (Table S1).…”
Section: Discussionsupporting
confidence: 84%
“…A previous study found that invasive species in their native ranges produced more biomass under heavy shading compared to non-invasive species (van Kleunen et al, 2011). Liu et al (2019) compared high and low salinity ecotypes of invasive and native species and found that the natives had greater costs of salt tolerance. Moreover, the invasive species had higher overall tolerance to other stressors, but lowsalinity ecotypes of native species had the lowest tolerance (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the root allocation is affected more strongly by variation in soil nutrients [ 73 ], the A. ochroleuca showed more allocation to root in the abandoned fields habitat which attained the highest content of nitrogen. Therefore, this suggests that A. ochroleuca in abandoned fields was responding to combined stressful conditions; possibly salinity and anthropogenic stresses rather than to a resource limitation [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have been conducted on the effects of salt stress on the morphology and physiology of invasive and native individually ( Mao et al., 2016 ; Baniasadi et al., 2018 ; Liu et al., 2019 ). However, little research has focused on whether the competitive effects between invasive and native species are affected by salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, salinity could influence invasion success, i.e., high salinity might increase the relative competitive ability of either native or invasive species depending on their tolerance ( Al Hassan et al., 2016 ). Previous studies have demonstrated that salinity can enhance the replacement of native plants by invasive plants ( Liu et al., 2015 ; Bollen et al., 2016 ; Legault et al., 2018 ), but salinity also can inhibit the establishment and performance of some invasive plants ( Qi et al., 2017 ; Liu et al., 2019 ). Therefore, whether salinity can promote the invasion of exotic species is debatable.…”
Section: Introductionmentioning
confidence: 99%